Signal transduction during aluminum-induced secretion of organic acids in plants - H. He; L. He; M. Gu (Biologia Plantarum, 2015)
An excess of aluminum (Al) is a major factor limiting crop production in acidic soils. Secretion of organic acids (OAs) from the root apex of diverse plant species or genotypes via activation of anion channels has been recognized as the most important mechanism of Al exclusion. Citric, oxalic, and malic acids are the most effective OAs in detoxifying Al. In this review, we summarize biochemical properties of OAs secreted by plants. We also highlight the molecular mechanisms of Al signal perception, Al transport, signal regulators associated with OAs secretion, as well as interactions between Al and hormone signaling pathways. Based on a comprehensive understanding of the relationship between signal modulators and regulation of expression of relevant genes, a signal transduction model for Al-induced OAs secretion is proposed.